Guidelines for the use of bone metabolic markers in the diagnosis and treatment of osteoporosis (2012 edition) - Nishizawa, Yoshiki; Ohta, Hiroaki; Miura, Masakazu; Inaba, Masaaki; Ichimura, Schoichi; Shiraki, Masataka; Takada, Junichi; Chaki, Osamu; Hagino, Hiroshi; Fujiwara, Saeko; Fukunaga, Masao; Miki, Takami; et al. (Journal of bone and mineral metabolism, 2013)
Recently the clinical application of bone metabolic markers has achieved significant progress and the measurements of these indices give us a better understanding of the pathogenesis of osteoporosis. Bone metabolic markers were adapted to select drug treatment for osteoporosis and to evaluate drug efficacy. Therefore, the proper application and assessment of bone metabolic markers in clinical practice is very important. To achieve these aims, the committee on the guidelines for the use of biochemical markers of bone turnover in osteoporosis authorized by the Japan Osteoporosis Society has summarized recent progress in bone markers and proposed the proper utilization of bone markers. Although the use of bone metabolic markers now has an important role in the daily management of osteoporosis, their use in Japan is still insufficient because of insurance coverage limitations. Since the Japan Osteoporosis Society first created the 2001 guidelines, new bone metabolic markers have been introduced into clinical practice. The availability of new osteoporosis treatments that promote bone formation has changed the clinical application of bone metabolic markers in current practice. Therefore, revisions to the current clinical practice are needed which led to the proposal to create these new 2012 guidelines.